PERBANDINGAN PEMBERIAN JUS BELIMBING WULUH (AVERRHOA BILIMBI) DAN JUS MENTIMUN (CUCUMIS SATIVUS) TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI PUSKESMAS AIR DINGIN KOTA PADANG - Vina Novela; Cici Apriliani; Mutia Devega Busli (LLDIKTI Wilayah X, 2023)
The type of this research was a quantitative method, namely Quasi Experimental Design in the form of Posttest only group design. It was conducted on July 2021 in Air Dingin Community Health Center. The population was 895 respondents with hypertension. The samples 20 people, namely 10 people in the group who drank star fruit juice and 10 people in the group who drank cucumber juice. The data was collected by observation sheets. Then, it was processed and analyzed by using univariate and bivariate analysis statistical with independent sample T-test. The results of this research showed that the average blood pressure in hypertensive patients who were given star fruit juice was 147.50 mmhg and sd was 9.20 and given cucumber juice was 141.50 mmhg and sd was 5.79. There was no difference in blood pressure in the group given star fruit juice (Averrhoa Bilimbi) and the group given cucumber juice (Cucumis Sativus) in hypertension sufferers in Air Dingin Community Health Center, Padang in 2021 with a p= 0.098. In short, there was no difference in blood pressure in the group given star fruit juice and cucumber juice. It is hoped that it will increase public knowledge about how to apply non-pharmacological treatments, such as consuming starfruit and cucumber, so that blood pressure is under control.